2018
DOI: 10.1021/acs.jced.8b00656
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of γ-CD-Modified TiO2 Nanoparticles and Its Adsorption Performance for Different Types of Organic Dyes

Abstract: In this work, γ-cyclodextrin-modified titanium dioxide nanoparticles (NPs) as an efficient nanoadsorbent were synthesized and used to remove methylene blue (MB), malachite green (MG), crystal violet (CV), disperse red 1 (DR1), acid blue 113 (AB113), and congo red (CR) dyes from synthetic wastewater. Characterization of cyclodextrin-functionalized TiO 2 nanoparticles using Fourier transform infrared, field-emission scanning electron microscopy, transmission electron microscopy, X-ray diffraction, energy-dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 79 publications
1
35
0
Order By: Relevance
“…Reusability study was performed to get information on the regeneration efficiency of the adsorbent for its potential future industrial applications 46 . After four consecutive adsorption/desorption cycles, the amount of dye removal decreased from 98% to 85%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reusability study was performed to get information on the regeneration efficiency of the adsorbent for its potential future industrial applications 46 . After four consecutive adsorption/desorption cycles, the amount of dye removal decreased from 98% to 85%.…”
Section: Resultsmentioning
confidence: 99%
“…Various parameters such as the chemical structure of adsorbate and adsorbent can affect the adsorption mechanism 46 . Based on the pH effect, BET analysis, adsorption kinetics, and thermodynamic studies, the mechanism of MG removal by the modified CTS nanosorbent is proposed in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a)). Mousavi et al . studied several organic dyes that included methylene blue (MB), acid blue 113 (AB113), disperse red 1 (DR1), MG and CV, showing that they could be removed using γ‐cyclodextrin‐modified TiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 85%
“…9(a)). Mousavi et al 49 studied several organic dyes that included methylene blue (MB), acid blue 113 (AB113), disperse red 1 (DR1), MG and CV, showing that they could be removed using -cyclodextrin-modified TiO 2 nanoparticles. The result indicated that the adsorption efficiency of dyes onto TiO 2 nanocomposite was MG > CV > MB > DR1 > AB113 at pH 4 to 7.…”
Section: Physical and Chemical Properties Of Synthetic Samplesmentioning
confidence: 99%